Accrediting your library program: what is it worth? - Smith, Kerry (2003)
This paper considers the role of accreditation in education for librarianship and information studies. It outlines the elements of core knowledge required in library education and the types of programs generally available. The accreditation programs of three international library associations: the American Library Association (ALA), the Chartered Institute of Library and Information Professionals (CILIP) and the Australian Library and Information Association(ALIA) are discussed. A case is presented for these associations to support the role of academic scholarship in librarianship. The paper concludes with a discussion of a number of the political issues involved in the accreditation process.